Clinical and pathological examinations on leptospirosis in cattle - Zabid Yener; İhsan Keleş (Eurasian Journal of Veterinary Sciences)
In the present study, leptospirosis was diagnosed in a cattle flock aged between 6 months and 2 years in the suburb of the city of Van. Seven animals were reported to have been died during the infection between December 1999 and January 2000 Clinically, icterus, haemoglobinuria, fever, leucocytosis, weight loss and anorexia were observed Histopathologically, necrotic hepatitis, haemoglobinuric nephrosis, vasculitis, haemorrhagic and catharal pneumonia, catharal enteritis, focal necrosis and hemosiderosis in spleen were seen. Certain diagnosis was based on the determination of leptospiral antigens by immunoperoxidase staining of sections obtained Irom liver, spleen, and kidney.